Analysis Of Islamic Business Ethics in Khizanah Gontor Bakery Production - Adzimi, Farkhan Rizky; Susilo, Adib; Cahyo, Eko Nur (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: This research is motivated by the phenomenon of many cases of poisoning in consumers after consuming food. Khizanah Gontor Bakery Pondok Modern Darussalam Gontor as a business actor can compile its system to continue to implement Islamic business ethics. The purpose of this study is to find out how the Khizanah Gontor Bakery system is in its production and to find out whether this business has implemented Islamic business ethics in its production system. Methodology: This study uses a qualitative method with a type of field research. Data was collected through interviews and observations. This research method is descriptive qualitative which analyzes the Implementation of Islamic Business Ethics in Khizanah Gontor Bakery Business Production. Findings: The results of the study show that Khizanah Gontor Bakery's business production is in accordance with the principles of Islamic business ethics. Business actors use good and halal raw materials for consumption. In their work system, staff and employees have also implemented Islamic ethical principles in them such as unity, justice, will, responsibility and also virtue. Even with the principle of sincerity, Khizanah Gontor Bakery staff carry out all tasks and develop their factory without any salary for them and with full sincerity. This principle is held firmly by the staff and does not commit any fraud in any of its production.